PERAN PENDIDIKAN KEWARGANEGARAAN DALAM MENINGKATKAN KESADARAN DEMOKRASI MAHASISWA - wildan; Syamzaimar (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
Civic Education (PKn) has a strategic role in fostering democratic awareness among adolescents as the future generation of the nation. This study aims to analyze how PKn learning can improve students’ understanding and participation in democracy. The method used is a descriptive quantitative approach through a survey of senior high school students.The results show that most students already have a fairly good understanding of democratic concepts, such as citizens’ rights and responsibilities, tolerance, and participation in national life. However, their level of involvement in socio-political activities remains relatively low. This is influenced by learning methods that still tend to be conventional and the lack of contextual learning implementation.In addition, the development of technology and social media poses challenges, as it can influence adolescents’ perspectives on democratic issues. Therefore, innovation in PKn learning is needed, such as the use of discussion methods, simulations, and case studies, as well as strengthening digital literacy so that students are able to think critically and actively participate in democratic life.